ICT-Based Authentic Assessment System Development to Measure Students’ Responsibility, Cognitive, and Teamwork Skill - Setiyadi, Hafid; Isnaeni, Wiwi; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2021)
The authentic assessment is a teacher’s challenge. The cognitive aspect is central of the continuity in learning development because authentic assessment is considered complicated to implement. The aim of the research is to produce an authentic ICT-based assessment system that is feasible and effective. The research method uses a one group pretest-posttest design with data collection techniques in the form of observation, interviews, questionnaires, documentation, and tests for 131 fifth grade students with type of development is ADDIE stages. The tools that have been developed are validated and revised according to the suggestions of the media and material validators which are then tested with subjects outside the large group sample before applied in the large group test. The validation results show that the validity of the material is 95.83% and the validity of the media is 97.5% with very decent criteria, observation analysis of responsibility attitude is 88% and cooperation skills 93% with very good criteria. The large group test analysis on the pretest-posttest measures critical thinking skills as part of cognitive which shows the percentage of completeness (KKM>75) of 85% with an N-Gain score of 0.68 in the medium category and received criteria quite effective. Based on the results, it is concluded that an authentic ICT-based assessment instrument is feasible and effective to use to measure the cognitive competence, attitude of responsibility, and cooperation of fifth graders. The application of ICT-based authentic assessment system can measure students’ achievement accurately. ICT-base authentic assessment system developed can be used with flexible in line with the needs of teachers.